LEGAL NORMS OF THE INTERNET INFORMATION ENVIRONMENT IN UZBEKISTAN: PROBLEMS AND SOLUTIONS (TAMADDUN NURI JURNALI, 2025)
This article examines the legal foundations of internet journalism in the Republic of Uzbekistan, focusing on the existing legislation, practical challenges, and prospects for development. Special attention is given to issues of freedom of speech, information security, the legal status of journalists and bloggers, and measures against cybercrime. The study also highlights gaps in current laws, the legal awareness of media professionals, and offers potential solutions based on international experience.